PROSES PENETAPAN DISMISAL TERHADAP MASUKNYA SUATU GUGATAN DI PENGADILAN TATA USAHA NEGARA SAMARINDA - Yessi Gasella (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTOne of the distinctive features of the State Administrative Court that distinguishes it from other courts is the process of dismissal through consultative meetings by the Chairman of the State Administrative Court in accordance with Article 62 of the Law on State Administration Courts. Dismissal process is a process of research on the lawsuit that entered in the State Administration court conducted by the Chairman of State Administrative Court at the second stage (two) or after the administrative research phase is implemented.The procedures of the State of Samarinda are in accordance with the applicable Standard Operation Procedure in Samarinda in accordance with the provisions of Article 62 of Law Number 5 Year 1986 concerning the State Administrative Court in both the escaped and non-qualified lawsuits. Before a lawsuit can be accepted, it must first go through a process of dismissal by the Chairman of the State Administrative Court of Samarinda with a letter of lawsuit approval, by law Number 5 of 1986 on the State Administrative Court.Key – Words : dismissal, lawsuit, administrative court